Anti-inflammatory effects of phytosphingosine-regulated cytokines and NF-kB and MAPK mechanism: Anti-inflammatory effects of phytosphingosine - Sung, Mikyung; Lim, Sojung; Park, Seungwon; Choi, Yongjin; Kim, Sangchul (Cellular and Molecular Biology, 2024)
Phytosphingosine (PHS) is a major component of the skin barrier and a multifunctional physiologically active substance. This study aimed to investigate the types of cytokines regulated by PHS, their anti-skin inflammatory effects, and their anti-inflammatory mechanisms. RAW264.7 cells stimulated with Lipopolysaccharides (LPS) were treated with PHS to measure inflammatory factors such as nitric oxide (NO) and prostaglandin E2 (PGE2), and gene expressions of inducible NO synthase (iNOS) and cyclooxygenase-2 (COX2) were confirmed by q-PCR. Cytokines regulated by PHS against LPS-induced inflammation were found through cytokine array, and each factor was reconfirmed through ELISA. Western blot was performed to confirm anti-inflammatory mechanism of Iκbα and MAPK. To confirm anti-skin inflammatory efficacy, HaCaT cells stimulated with TNF-α/IFN-γ were treated with PHS, and TARC, IL-6, and IL-8 were detected by ELISA. PHS suppressed the gene expression of iNOS and COX2, which were increased by LPS, and suppressed NO and PGE2 production. Through cytokine array, it was confirmed that IL-6, IL-10, IL-27 p28/IL-30, IP-10, I-TAC, MCP-5, and TIMP-1 increased by LPS were decreased by PHS. PHS inhibited NF-κB signaling by inhibiting LPS-induced NF-κB nuclear migration and p-Iκbα-mediated Iκbα degradation, and inhibited p38, ERK, and JNK signaling pathways. PHS reduced the production of TARC, IL-6, and IL-8 increased by TNF-α/IFN-γ. These results indicate PHS has anti-inflammatory effects via the suppression of inflammatory factors and pro-inflammatory cytokines through the NF-κB and MAPK pathways. Moreover, these results may explain beneficial effects of PHS in the treatment of skin inflammatory conditions induced by TNF-α/IFN-γ.